Effects of oral meloxicam administration to beef cattle receiving lipopolysaccharide administration or vaccination against respiratory pathogens - Rodrigues, M. C. [UNESP] (2015)
This study evaluated the effects of oral meloxicam administration on metabolic, inflammatory, and acute-phase responses of beef cattle receiving a lipopolysaccharide (LPS) challenge (Exp. 1; d - 1 to 6) or vaccinated against respiratory pathogens (Exp. 2; d 7 to 21). Twenty-one Angus steers (n = 11) and heifers (n = 10) were housed in individual pens on d - 15 and were offered free-choice water, mineral-vitamin mix, and hay until d 21. In Exp. 1, cattle were ranked on d - 1 by sex and BW and assigned to 1) oral meloxicam administration (1 mg/kg BW daily) from day - 1 to 6 (MEL8), 2) oral meloxicam administration (1 mg/kg BW) on d 0 and oral lactose monohydrate administration (1 mg/kg BW) on d - 1 and from d 1 to 6 (MEL1), or 3) oral lactose monohydrate administration (1 mg/kg BW daily) from d - 1 to 6 (CON). On d 0, cattle received an intravenous LPS bolus (0.5 mu g/kg BW) concurrently with treatment administration. Rectal temperature (RTEMP) was assessed, and blood samples were collected at -2, 0, 2, 4, 6, 8, 12, 16, 24, 36, 48, 60, 72, 96, 120, and 144 h relative to LPS administration. No treatment effects were detected (P >= 0.36) for RTEMP, concentrations of serum tumor necrosis factor a (TNF alpha), plasma haptoglobin, cortisol, insulin, and leptin, as well as blood mRNA expression of TNF alpha and cyclooxygenase-2, although all variables increased (P < 0.01) across treatments after LPS administration. In Exp. 2, cattle received the same treatments that they were assigned to in Exp. 1 from d 7 to d 13 and were vaccinated against respiratory pathogens concurrently with treatment administration on d 8. Blood samples were collected, and RTEMP was assessed as in Exp. 1 in addition to 168, 240, and 336 h relative to vaccination. No treatment effects were detected (P >= 0.26) for RTEMP, the same plasma and serum variables evaluated in Exp. 1, and serum concentrations of antibodies against Mannheimia haemolytica or serum titers against bovine respiratory syncytial virus, bovine herpesvirus-1, bovine viral diarrhea virus-1, and parainfluenza-3 virus. All variables increased (P < 0.01) across treatments after vaccination, except for serum TNF alpha and titers against bovine viral diarrhea virus-1 (P >= 0.40). Collectively, this study found no evidence that oral meloxicam administration, at the doses and intervals utilized herein, mitigated the metabolic, inflammatory, and acute-phase reactions elicited by LPS administration or vaccination against respiratory pathogens.